The intensity of biofilm formation by heterotrophic bacteria isolated from soil ferrosphere - Tkachuk, Nataliia; Zelena, Liubov (Ecological Questions, 2022)
The intensity of biofilm formation by heterotrophic bacteria possessed ammonifying ability (Bacillus simplex ChNPU F1, Streptomyces canus NUChC F2, Streptomyces gardneri ChNPU F3), ammonifying and iron-reducing ability (Fictibacillus sp. ChNPU ZVB1) previously isolated from soil ferrosphere was studied. Methods used: indirect measurement of the biomass of the bacterial biofilm using the adsorption/desorption of crystal violet, the aggregation test (to determine aggregation properties), the salt aggregation test (to determine hydrophobicity). The correlation analysis between the intensity of biofilm formation and aggregation of strains showed a significant positive correlation. The studied strains of microorganisms did not show high adhesive properties, they were moderately-adhesive (B. simplex, S. canus and S. gardneri) and weakly-adhesive (Fictibacillus sp.). It is supposed that the role these bacteria in the microbial damage of materials is determined preferably by bioelectrochemical reactions (iron-reducing bacteria) and the production of corrosive and/or antimicrobial metabolites (ammonifying and iron-reducing bacteria), but not by the biofilms formation. The prospect of further research is to analyze the antagonistic properties and biofilm formation of heterotrophic bacteria under co-cultivation conditions, in particular, with sulfate-reducing bacteria.